DAMPAK SOSIAL NIKAH SIRRI - Muhammad Budiono (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2014)
Abstract: This article discusses the social impact of unregistered (sirri) marriage. The unregistered marriage is a marriage conducted by a guardian of woman with a man and witnessed by two witnesses. However, it is not reported or not recorded in the Office of Religious Affairs (KUA). The unregistered marriage is causing a positive social impact and a negative social effect. The positive social impact of which is to minimize the presence of free sex, as well as the development of AIDS, HIV and other sexually transmitted diseases and to reduce the burden or responsibility of a woman who becomes the backbone of the family. The negative social impacts are cheating is a natural thing. There will be many cases of polygamy, namely the unclear status of wife and child in front of law in Indonesia and the people around, the sexual abuse of womanhood because it is considered as an outlet for temporary lust for a man, it is hard for a wife to assert her rights, it is difficult to determine the ownership of child if there is a problem because of divorce, the difficulties of obtaining a divorce certificate, and causing a scandal.Abstrak: Artikel ini membahas tentang dampak social nikah sirri. Nikah sirri adalah pernikahan yang dilakukan oleh wali pihak perempuan dengan seorang laki-laki dan disaksikan oleh dua orang saksi, tetapi tidak dilaporkan atau tidak dicatatkan di Kantor Urusan Agama (KUA). Nikah sirri adalah menyebabkan dampak sosial yang positif dan dampak negatif. Dampak sosial yang positif diantaranya adalah meminimalisasi adanya seks bebas, serta berkembangnya penyakit AIDS, HIV maupun penyakit kelamin yang lain dan mengurangi beban atau tanggung jawab seorang wanita yang menjadi tulang punggung keluarganya. Adapun dampak negatifnya adalah: Berselingkuh merupakan hal yang wajar, akan ada banyak kasus poligami yang akan terjadi, tidak adanya kejelasan status isteri dan anak baik di mata hukum di Indonesia maupun di mata masyarakat sekitar, pelecehan seksual terhadap kaum hawa karena dianggap sebagai pelampiasan nafsu sesaat bagi kaum Laki-laki, sulit menuntut hak waris bagi istri, sulit menentukan kepemilikan anak apabila ada masalah gara-gara cerai, jika dicerai tidak akan memiliki surat cerai dan surat janda dari pengadilan dan menimbulkan fitnah.